The effect of some chemical disinfection solutions on the color stability of vinyl addition cured silicon - Ibtehal H AL -Zubaidy (University of Mosul, College of Dentistry, 2017)
Aims: The study investigated the effect of curing methods and the effect of some chemical disinfection solution on the color parameters of the vinyl addition silicon maxillofacial materials. Materials and methods: 30 samples were made from maxillofacial silicon rubber. The samples (20*10*3)mm length, width, and thickness, were divide into two group ( cold and hot curing )15 sample for each group , 5 sample for each disinfection solution that used in this study and then tested to record the color parameters . Results: The result showed there was significant differences between (group 1 and group 2 ) in all L,a,b values and more changes was found in group 1(cold cure ) except in L1 and b3 the more changes was found in group 2(hot cure ). the more color changes was found in the samples that immersed in Sodium hypochlorite. the chlorhexidine showed less value of color changes than the other type. Conclusion:Translucency of the cold cured samples was higher than that of the heat cured samples, due to the effect of processing heat . the more color changes was found in the samples that immersed in Sodium hypochlorite. the chlorhexidine showed less value of color changes than the other types because it chemically inert and acting through saturation.